Infantile Spasms and ACTH Dosage - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Results of corticotropin treatment of 33 patients with infantile spasms are reported from the Instituto Clinica Pediatrica, Universita di Siena, Italy.